El proyecto arquitectónico como un problema de investigación (2013)
This paper discusses the pedagogical practice of architectural design from the research point of view as a way to transcend the traditional teaching, which has historically been rooted in architectural education. The research from which this paper is derived is exploratory and the main objective establishes methodological processes identification to develop the practice of architectural design and it raises the question of how to solve the need for rigor and specificity required in a scientific process in architecture. This process must be teachable and learnable, repeatable and reportable, in order to overcome the uncertainty and anxiety of facing architectural design problems from the void. As the main result of the study, a logical process is obtained to address an architectural problem from the perspective of the research work process. This text is part of the current debate about architecture teaching - learning processes and it traces questions about the relationship between architecture and its research component.